Performance Evaluation of Direct Torque Control with Permanent Magnet Synchronous Motor - Bindeshwar Singh (Bulletin of Electrical Engineering and Informatics, 2012)
The direct torque control theory has achieved great success in the control of permanent magnet synchronous motor. A Direct Torque Control (DTC) scheme of Permanent Magnet Synchronous Motor (PMSM) is presented. Based on in-depth analysis of PMSM mathematical model in abc frame and frame are established and the operation principle of DTC-SVPWM system, the relationships between the torque and fundamental components. A novel space vector pulse width modulation (SVPWM) method which has a feature of low harmonic is proposed. The proposed method is adopted to implement the direct torque control (DTC) of a three-phase PMSM. A large number of simulation results show that the DTC System of PMSM has fast response and good dynamic performance. Aiming at the direct torque control in PMSM Drives, in this paper explained the theoretical basis of the direct torque control (DTC) for PMSM firstly. Then explained the difference between the applications of DTC-SVPWM to PMSM. Finally the MATLAB/Simulink models were developed to examine the DTC- SVPWM for PMSM. The simulation results is presented in this paper.